2015
DOI: 10.1371/journal.pone.0139057
|View full text |Cite
|
Sign up to set email alerts
|

GlycA, a Pro-Inflammatory Glycoprotein Biomarker, and Incident Cardiovascular Disease: Relationship with C-Reactive Protein and Renal Function

Abstract: ObjectiveGlycA is a novel nuclear magnetic resonance spectroscopy-measured biomarker of systemic inflammation. We determined whether GlycA is associated with incident cardiovascular disease (CVD) in men and women, examined whether this association with CVD is modified by renal function, and compared this association with high sensitivity C-reactive protein (hsCRP).Research design and methodsA prospective cohort study was performed among 4,759 subjects (PREVEND study) without a history of CVD and cancer. Incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…Consistent with our findings, Gruppen et al (14 ) found in their prospective cohort study, PREVEND, of 4759 subjects free of overt CVD but including a large subgroup who had albuminuria, that GlycA was associated with CVD events independently of renal function. The association of GlycA with incident CVD was as strong as that of hsCRP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, Gruppen et al (14 ) found in their prospective cohort study, PREVEND, of 4759 subjects free of overt CVD but including a large subgroup who had albuminuria, that GlycA was associated with CVD events independently of renal function. The association of GlycA with incident CVD was as strong as that of hsCRP.…”
Section: Discussionsupporting
confidence: 93%
“…GlycA is a composite biomarker that senses the integrated concentrations and glycosylation states of several of the most abundant acute-phase proteins in serum. The limited available information about GlycA finds that it is associated with incident CVD and risk for type 2 diabetes mellitus in initially healthy women (12)(13)(14).…”
mentioning
confidence: 99%
“…GlycA, the NMR signal derived from multiple inflammatory glycoproteins, was demonstrated to predict future CVD and T2DM (Table 2) [71][72][73]. GlycA was shown to be related to the leptin/adiponectin ratio, suggesting that adipose tissue-associated low-grade inflammation could be involved in the regulation of inflammatory glycoproteins [49].…”
Section: Glycoprotein Assays and Cardiometabolic Disordersmentioning
confidence: 99%
“…In the Women's Health Study (WHS), GlycA was associated with CVD events, independent of traditional risk factors [71]. In the Prevention of Renal and Vascular End-stage Disease (PREVEND) study, GlycA was associated with incident CVD, defined as the combined end-point of CV morbidity and mortality, independent of clinical and lipid measures as well as renal function [72]. Baseline concentrations of GlycA in the Justification for the Use of Statins in Prevention: an Interventional Trial Evaluating Rosuvastatin (JUPITER) trial were significantly associated with incident CVD events, even when adjusting for established risk factors and a family history of premature coronary heart disease [73].…”
Section: Glycoprotein Assays and Cardiometabolic Disordersmentioning
confidence: 99%
“…GlycA is regarded as a marker of low-grade systemic inflammation (16)(17)(18). Evidence has been accumulating that GlycA may predict CVD as well as incident type 2 diabetes mellitus (T2DM) (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%